Authentic leadership and its interactions with the compassion and humility of employees - Oliveira, Márcio (2021)
By the increasing recognition that the scientific and practical communities attribute humility and compassion as influencing organisational performance, this study aims to understand whether the exercise of authentic leadership influences these constructs. For this purpose, using a quantitative study, a questionnaire was applied to employees of small and medium-sized Portuguese companies who are directly subordinated to the top management of these companies in the course of their professional activity. This research empirically validates the theoretical arguments that suggest that authentic leadership is related to humility and compassion (the latter, measured based on the dimensions of kindness, common humanity, full attention, indifference, detachment and separation) and demonstrates that subordinates are essential resources to help organisations face competitive challenges, taking advantage of their employees' potential and promoting organisational efficiency and competitive advantages over the competition.